2020
DOI: 10.1038/s41467-020-20260-7
|View full text |Cite
|
Sign up to set email alerts
|

An immune checkpoint score system for prognostic evaluation and adjuvant chemotherapy selection in gastric cancer

Abstract: Immunosuppressive molecules are extremely valuable prognostic biomarkers across different cancer types. However, the diversity of different immunosuppressive molecules makes it very difficult to accurately predict clinical outcomes based only on a single immunosuppressive molecule. Here, we establish a comprehensive immune scoring system (ISSGC) based on 6 immunosuppressive ligands (NECTIN2, CEACAM1, HMGB1, SIGLEC6, CD44, and CD155) using the LASSO method to improve prognostic accuracy and provide an additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 48 publications
(20 reference statements)
2
63
0
Order By: Relevance
“…For example, PD-1 and ICOS were strongly expressed on CD4 + T cells, whereas TIM-3 and VISTA were strongly expressed on macrophages. Furthermore, immunoregulatory protein expression was highly variable across CTCL patients, in line with previous reports ( 40 , 49 ); some patients had high expression of numerous markers whereas others had low expression of all markers. This degree of heterogeneity highlights the importance of analyzing functional immune molecules in individual patients and larger patient cohorts.…”
Section: Discussionsupporting
confidence: 91%
“…For example, PD-1 and ICOS were strongly expressed on CD4 + T cells, whereas TIM-3 and VISTA were strongly expressed on macrophages. Furthermore, immunoregulatory protein expression was highly variable across CTCL patients, in line with previous reports ( 40 , 49 ); some patients had high expression of numerous markers whereas others had low expression of all markers. This degree of heterogeneity highlights the importance of analyzing functional immune molecules in individual patients and larger patient cohorts.…”
Section: Discussionsupporting
confidence: 91%
“…patients (Cho et al, 2011;Cai et al, 2020Wang et al, 2020: Figure 4H). Therefore, we included PS-score as an effective indicator and other clinical characteristics, into Cox regression analysis and found that PS-score and stage were both two factors that independently affected the prognosis of GC patients (Table 2).…”
Section: Development and Validation Of A Gene Signature Based On Pyroptosis-related Clustersmentioning
confidence: 99%
“…Despite this amount of data, results are still confounding. Baseline PNI (prognostic nutritional Index), for example, has been reported as useful in some retrospective studies [ 66 ], but questioned [ 67 ] or not confirmed in others [ 68 ]. In melanoma patients, overweight or obese patients may derive benefit in terms of progression-free survival (PFS), but not in overall survival (OS).…”
Section: Nutritional Care During Immunotherapy: Does the Boundless Prairie Have A Fence?mentioning
confidence: 99%